The higher education teaching practices in the public Universities of Bangladesh - Khan Sarfaraz Ali; Ida Hindarsah (SEAN Institute, 2024)
Better teaching-learning practice ensures effective learning of scholars and further exhibits teachers’ skills and efficiencies in education. This research aims to analyze the teaching-learning practices of public universities in Bangladesh. This study followed the survey method for data collection and a complete of 98 questionnaires were analyzed giving a response rate of 90.74 percent. This study used convenience sampling for sample selection. The respondents of the study were the teachers from different faculties of public universities in Bangladesh. The collected data were analyzed using SPSS version 26. The result indicates that the upper level of education within the country still follows the pedagogy sort of teaching. Among the respondents’ 59.2 percent haven't any idea about the andragogy sort of teaching and 71.4 percent haven't any idea about the heutagogy sort of teaching. Moreover, 44.9 percent of the respondents believe that students’ learning is assured through the pedagogy style. Simultaneously, Focus give-and-take (FGD) and Key Informant Interview (KII) methods were also applied for in-depth data collection. Finally, the study implications, limitations further suggestions are discussed accordingly during this report.